Factors affecting misdiagnosis of non-complicated and complicated appendicitis in pediatric patients - Puspitasari, Eva; Barmadisatrio, Barmadisatrio; Hariastawa, IGB Adria (Journal of Neonatal Surgery, 2025)
Background: Diagnosing appendicitis in children remains challenging due to difficulties in expressing complaints, localizing pain, nonspecific symptoms, and broad differential diagnoses. Diagnostic supports like ultrasound and CT scans are not routinely performed on children. This necessitates data analysis to identify factors influencing misdiagnosis. Methods: This retrospective cross-sectional study analyzed pediatric appendicitis patients undergoing surgery at General Hospital Dr. Soetomo, Surabaya, from January 2023 to September 2024. Data from 84 patients who met inclusion criteria were collected from electronic medical records. Bivariate analysis assessed relationships between age, clinical symptoms, leukocyte levels and Neutrophil-to-Lymphocyte Ratio (NLR) with appendicitis misdiagnosis. Results: Out of 84 subjects, 48 subjects (57.1%) had non-complicated appendicitis and 36 (42.8%) had complicated appendicitis. Misdiagnosis occurred in 11% of patients. Analyses revealed no significant associations between age (p=0.391), clinical symptoms, leukocyte levels (p=0.843), NLR (p=0.273) and appendicitis misdiagnosis. Conclusion: There is no significant association between age, clinical factors, leukocyte levels and NLR with the incidence of misdiagnosis of non-complicated and complicated appendicitis in pediatric patients.